THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE PUSKESMAS ACCREDITATION POLICY IN BAUBAU CITY IN 2022 - Wahyuni, Sri; Sinta, Niska Salsiani; Amiruddin, Ahmad (Sean Institute, 2022)
Puskesmas as the spearhead of health services and gate keeper in formal health services and referral screening, must be able to provide quality services in accordance with service standards and compe-tency standards. To support this, one of the policy directions and strategies of the Ministry of Health is to improve equitable access and quality of health services, especially in Puskesmas, name-ly through an accreditation policy. This study aims to identify the factors that influence the effec-tiveness of the implementation of the accreditation policy at the Baubau City Health Center. This type of research is a qualitative research with a single embedded case study design. This study uses a Consolidated Implementation Research Framework (CFIR) covering four main domains, used to guide the collection and analysis of qualitative data as recommended by Damschroder and Lowery (2009). This research was conducted at health centers that have different accreditation statuses, namely Primary Accreditation and Intermediate Accreditation. Informants were interviewed using The Consolidated for Implementation Research (CFIR) framework as a guide in collecting and ana-lyzing qualitative data. This research was carried out from April to May 2022. The research subjects consisted of 10 people consisting of an accreditation team from 2 Puskesmas in Baubau City, name-ly Kadomoko Health Center and Bukit Wolio Indah Health Center. The results show that the fac-tors from CFIR that most dominantly affect the effectiveness of the implementation of accredita-tion policies are available resources, implementation climate, as well as external policies and incen-tives, as well as positive acceptance of accreditation policies because they are felt to provide many benefits and advantages, especially in terms of developing a quality management system. and efforts to improve service performance at the Puskesmas. Based on the results of this research, it is neces-sary to follow up in the form of policies from the Health Office regarding the availability of re-sources at the puskesmas, as well as develop broader research in several Puskesmas and the Health Office in order to better describe the problems related to policy implementation in a holistic man-ner.